Holmium LASER in Comparison with Transurethral Resection of the Bladder Tumor for Non-muscle Invasive Bladder Cancer: Randomized Clinical Trial with 18-month Follow-up - Razzaghi , Mohammad Reza; Mazloomfard, Mohammad Mohsen; Yavar, Mahmoud; Malekian, Sheida; Mousapour, Pouria (Urology Journal, 2021)
Purpose: To evaluate the safety and efficacy of holmium LASER resection of the bladder tumor (HoLRBT) vs. transurethral resection of bladder tumor (TURBT) as the first treatment modality for non-muscle-invasive bladder cancer (NMIBC). Materials and Methods: Eighty-eight patients with primary non-muscle invasive bladder cancer were allocated randomly in two groups who were treated with HoLRBT or TURBT. The intraoperative and postoperative characteristics and complications of the HoLRBT and TURBT groups were compared. The data of operation time, obturator nerve reflex rate, bladder perforation, bladder irrigation, catheterization time, hospital stay, and 1, 3, 6, 12, 18 months recurrence free survivals were considered in two groups. Results: There was not significant difference in operative duration among the two groups. Compared with the TURBT group, HoLRBT group had less intraoperative and postoperative complications, including obturator nerve reflex, transient hematuria and postoperative bladder irritation. There were no significant differences among the two groups in the transfusion rate and occurrence of urethral strictures. Patients in the HoLRBT group had less catheterization and hospitalization time in comparison to those in the TURBT group. There were no significant differences in the overall recurrence rate among the TURBT and HoLRBT groups. Conclusion: HoLRBT can be regarded as a safe and efficient method with several advantages over TURBT. HoLRBT can be used as an alternative procedure for TURBT in patients with non-muscle invasive bladder cancer.